The influence of online learning readiness on student retention in Malaysian private higher education institutions - Khong, Eng Mun (2023)
The global educational landscape underwent significant changes with the onset of the COVID-19 pandemic. Many higher education institutions (HEIs) proceed with a rapid shift from traditional face-to-face learning to online platforms. Students face numerous challenges in adapting to online learning, resulting in low satisfaction and high dropout rates. Thus, students must possess online learning competencies that enable them to navigate online learning environments effectively. Drawing on Tinto’s Social Integration Model (SIM), this study examines the relationships between student online learning readiness, student satisfaction, institutional support, and student retention in private HEIs. The study employed a cross-sectional survey design, utilising a combination of purposive and quota sampling to collect data from students who have experience with online learning in private HEIs. SmartPLS software was employed to examine the hypothesised relationships. The Structural Equation Model (SEM) analysis comprised of 419 voluntary student participants from private HEIs. The results revealed that student online learning readiness (encompassing technical, communication, social competencies with classmates and instructor, and self-regulated learning) positively influenced student satisfaction, which, in turn, influenced student retention. Further, student satisfaction partially mediated the relationship between technical competencies and retention and fully mediated the relationships between social competencies with classmates, social competencies with instructors, and self-regulated learning competencies, and retention. Surprisingly, institutional support did not significantly moderate the relationship between student satisfaction and retention, contrary to the initial hypothesis. However, a notable positive association was found between institutional support and student retention. These findings hold substantial implications for higher education institutions, policymakers, and society, offering valuable insights into students’ perceptions of their online learning competencies and satisfaction. The insights of the study provide educational institutions with crucial information to enhance student interest and retention from an online learning perspective. Keywords: Online learning readiness, Competencies, Satisfaction, Institutional Support, Student Retention